Carbon Nanofoam by Pulsed Electric Arc Discharges - David Saucedo-Jimenez; Isaac Medina-Sanchez; Carlos Couder Castañeda (Advances in Materials Science and Engineering)
The aim of this article was to report the carbon nanofoam synthesis by a new method and a new catalytic mixture. Using the pulsed electric arc discharge method, carbon nanofoam was synthesized. The synthesis was carried out in a controlled atmosphere at 200 torr of hydrogen pressure. The pulsed electric arc discharge was established between two graphite electrodes with 22.8 kVA of power and 150 A DC current; the cathode was relatively motionless and was made of a pure carbon rod of 6 mm diameter, and the spinner anode was a pure carbon disc spinning at 600 rpm; over the disc was an annular cavity where the new catalytic mixture of 93.84/2.56/1.43/0.69/1.48 of C/Ni/Fe/Co/S molar fraction was deposited in a geometrically fixed way by 8 catalytic mixture blocks and 8 empty spaces, and the discharge frequency was 80 Hz. After the synthesis was made, the resulting products were deposited on the electrodes, proving that our method can synthesize different carbon nanostructures easily and at low cost.